Contributions to Anatolian History and Numismatics 11. Eagle omens: Foundations of Cities and Cults at the behest of Zeus - Johannes Nollé (Gephyra, 2015)
This paper deals with a mythological motif that we fairly frequently come across both in ancient literature and on coin images. Unfortunately, in the case of the coins the representation of this motif is mostly overlooked, not recognised or misinterpreted, so that it may be helpful for historians as well as for numismatists to take another look at such coins. The motif in question is linked with the foundation of cities: an eagle sent by Zeus swoops down from heaven, robs some sacrificial meat or bones burning on an altar and carries its prey away to a place, where Zeus wants a city to be founded by the very man who is offering the sacrifice. The motif of an eagle purloining sacrificial meat is very old; evidence for it takes us back to the times of the Greek poet Archilochos who may have got knowledge about it from Aesop's fables, which have their roots partly in Near Eastern traditions. The use of the motif in connection with the establishment of a city, however, was particularly used in the Hellenistic epoch. In some way or other the founding of Alexandria near Egypt by Alexander the Great may have been the model, after which elsewhere similar stories were formed and came into circulation. Local legendry traditions of Alexandria, which may have come up already in Alexander's lifetime, tell us the story that Alexander was led by an eagle stealing sacrificial meat to a place, where, since time immemorial, Serapis had been venerated. With the establishment of this cult the founding of Alexandria was complete: the city had got its tutelary god. A similar story about the foundation of the city, probably unhistorical, emerged in Alexandria Troas. An eagle, strangely enough sent not by Zeus but by the local god Apollo Smintheus, guided Alexander to the place where he established this Alexandria. An eagle perching on thigh bones of a sacrificial animal is depicted on coins of the Phrygian cities of Blaundos and Amorion. This shows for sure that local lore associates the founding of these cities with the appearance of Zeus' eagle. In both cases Alexander the Great may be the founder of these cities, but this cannot be proved definitively. The example of Alexander the Great was soon after used for mythical stories about the establishment of cities by Seleucid kings. There are literal traditions reflected by coins that Antiocheia in Syria, its harbour Seleukeia Pieria and the nearby Laodikeia were founded by king Seleukos I, who was guided by Zeus' eagle to the right places. In the case of Laodikeia this mythological motif was combined with that of a city foundation after a successful hunt: after having slain a huge boar, Seleukos was led by an eagle and founded this harbour town. Also, the citizens of Antiocheia in Caria used the eagle motif to claim that their city, established by king Antiochos I, was founded at the behest of Zeus. The Hellenistic kings of Bithynia, too, made intensive use of such tales. King Nikomedes I founded his new residence town of Nikomedeia with the guidance of an eagle sent by a Zeus and of a snake, the sacred animal of Demeter. The corn goddess was the mistress of the area, where the new city was founded. Prusa near Mount Olympos was established by King Prusias I, after a successful hunt and an eagle portent. Perhaps already in Hellenistic times some cities, not founded by kings but by heroes, also made use of this eagle motif. One of them is Aphrodisias in Caria, whose local tradition about its establishment by the Assyrian king Ninos after an eagle portent, occurs only on scupltural reliefs, but can be clearly understood with the help of the parallel traditions discussed here. The city coinage of the small Lycian city of Arykanda reflects a foundation story, according to which the two eponymous heroes Arys and Kandys succeeded in taking a boar. When the two heroes were offering its head as a sacrifice, an eagle stole it and took it to the place where these two warriors founded Arykanda and named it after themselves. The use of the eagle story also has a very long tradition in Byzantion. The local legends record a myth about the foundation of Byzantion by the Thracian hero Byzas, who was led by an eagle to a rocky place, where he should found a new city. Previously the eagle had robbed the heart of Byzas's sacrificial animal. A city coin, that shows the head of Byzas on its obverse, depicts this eagle sitting on the rocks of soon-to-be Byzantion on its reverse. This coin was minted in the time of Caracalla, who became a "New Byzas" by his support for the mutilated and humilated city. Later on the eagle motif was used for Constantine's foundation of Constantinople. Finally, an example from the small Peloponnesian town of Kleonai reminds us that the eagle myth was also circulating in the Greek motherland. In conclusion, this paper discusses the question what these mythic tales were used for and how Greek city-founders combined or blended rational and mythic thought with each other.